Avaliação histológica da resposta inflamatória a cimentos de obturação endodôntica - Oliveira, Rodrigo Pagliari (2006)
Dentistry in our days has been working in an incessant manner so that its results be well-known. New techniques, new materials, ultimately, even if the indexes of dental decay still reach a number that characterize risk. Not only the evolution of the disease decay, but also the iatrogenic make it necessary to have endodôntic treatment that consists in the removal of all necrosis inflamed and infected material from the system of root channels, disinfection of the same system and its substitution by felling material. It also verifies, in the present day, the lack of consent among researchers, as to the ideal material to be used in the endodontic fillings. In this way, the present work aimed at the accomplishment of a comparative histological evaluation, through biological tests, according to criteria established by the International Dental Federation of three materials indicated for this end. In this experiment the following materials were tested: AHPlus, another endodontic material recently introduced to the market Epiphany and MTA, Aggregated Trioxide Mineral. Thirty (30) guinea-pigs were used (" Guinea Pig ") ten (10) for each material, divided in experimental periods of 30 and 90 days. Two (2) inter-bone implants were accomplished in each animal, in the lateral area to the mandible sínfisis, on the side of the incisive teeth. So as to condition the tested materials Teflon cups were used, as the sides served as control. Terminating the experimental periods, the animals were sacrificed and the specimens were prepared for routine histological exam. The results showed that MTA as much as the Epiphany cement presented biocompatibility characteristics according to the criteria adopted and AHPlus did not. The results allowed us to conclude, according to FDI and ADA /ANSI protocols, that the Epiphany and MTA materials are biocompatible, presenting biological conditions for their use as endodontic filling material.